Mapping the STEM-Creativity Nexus: A Bibliometric and SLR Analysis of Learning Models, Barriers, and Future Directions in Science Education - Bintan Nuril Irvaniyah; Parno Parno; Nina Diana Nawi (Universitas Muhammadiyah Surakarta, 2025)
This study aims to review the application of the STEM approach in improving creative thinking abilities in science education, using the Systematic Literature Review (SLR) method. A total of 26 articles retrieved from Scopus and Google Scholar databases were analyzed. The data visualization process was conducted using R Studio and Microsoft Excel to map related research trends. The results of the review showed that the application of STEM approaches is growing and gaining widespread attention from lecturers, teachers, researchers and education stakeholders globally, especially in Indonesia, Taiwan, Turkey and Germany. Indonesia dominates research in this area, mainly due to the influence of national policies and curricula that support STEM implementation. Various learning methods and models such as Project-Based Learning (PjBL), Inquiry-Based Learning (IBL), and Design-Based Learning have been integrated with the STEM approach and proven effective in improving students' creative thinking ability. Key barriers include limited time, insufficient resources and challenges in adapting curricula to support STEM implementation in specific subjects. Creativity is difficult to develop with just one short intervention; it requires a supportive social environment, repeated practice and greater freedom for exploration. As an innovative step, future research may consider integrating the Clarity Learning Model (CLM) as a new element to strengthen the learning structure. These findings provide important insights for educators and researchers in designing STEM-based learning that is more effective and relevant to future needs.